An EMG-Based Virtual Reality Application for Motor Rehabilitation - Melo, Mirella; Neto, José; Teixeira, João Marcelo; Gama, Alana; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2019)
Motor deficiency, congenital or acquired, occurs when the neuromotor system is compromised, such as, due to muscle damage. When this situation is reversible, physiotherapy is recommended, where the individual stimulates the impaired muscle until it gets back its functionality, partial or total. However, traditional therapy based on kinesiotherapy is admittedly a repetitive and monotonous treatment, sometimes discouraging patients to undertake the treatment. In view of this situation, this work aims to take advantage of immersion (virtual reality - VR) as an asset of stimulation and motivation. The proposal is a game, parameterized by the physiotherapist, who uses the muscular stimuli as input, which are captured by the electronic device developed, which is capable of amplifying the electromyographic signal (EMG), that is, the electric stimulus generated by the contracted muscle. Once the game was developed, user experiments were performed in order to confront EMG data captured during the treatment (a) using virtual reality and (b) without the use of virtual reality. The hypothesis raised and proven from statistical analyses with 99% of confidence, is that there is a greater performance by the user with the use of VR. Other quantitative metrics were also adopted for analysis such as symptoms, usability, hedonic quality, and Borg scale. In summary, this work illustrates a way to bring motivation and commitment to motor rehabilitation therapies by taking into account a powerful immersion which is VR.